Ribosome Shunting, Polycistronic Translation, and Evasion of Antiviral Defenses in Plant Pararetroviruses and Beyond - Pooggin, Mikhail M.; Ryabova, Lyubov A. (Frontiers in Microbiology, 2018)
Viruses have compact genomes and usually translate more than one protein from polycistronic RNAs using leaky scanning, frameshifting, stop codon suppression or reinitiation mechanisms. Viral (pre-)genomic RNAs often contain long 5'-leader sequences with short upstream open reading frames (uORFs) and secondary structure elements, which control both translation initiation and replication. In plants, viral RNA and DNA are targeted by RNA interference (RNAi) generating small RNAs that silence viral gene expression, while viral proteins are recognized by innate immunity and autophagy that restrict viral infection. In this review we focus on plant pararetroviruses of the family Caulimoviridae and describe the mechanisms of uORF- and secondary structure-driven ribosome shunting, leaky scanning and reinitiation after translation of short and long uORFs. We discuss conservation of these mechanisms in different genera of Caulimoviridae, including host genome-integrated endogenous viral elements, as well as in other viral families, and highlight a multipurpose use of the highly-structured leader sequence of plant pararetroviruses in regulation of translation, splicing, packaging and reverse transcription of pregenomic RNA, and in evasion of RNAi. Furthermore, we illustrate how targeting of several host factors by a pararetroviral effector protein can lead to transactivation of viral polycistronic translation and concomitant suppression of antiviral defenses. Thus, activation of the plant protein kinase target of rapamycin (TOR) by the Cauliflower mosaic virus transactivator/viroplasmin (TAV) promotes reinitiation of translation after long ORFs on viral pregenomic RNA and blocks antiviral autophagy and innate immunity responses, while interaction of TAV with the plant RNAi machinery interferes with antiviral silencing.